2009
DOI: 10.1093/hmg/ddp202
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association meta-analysis for total serum bilirubin levels

Abstract: Variation in serum bilirubin is associated with altered cardiovascular disease risk and drug metabolism. We aimed to identify genetic contributors to variability in serum bilirubin levels by combining results from three genome-wide association studies (Framingham heart study, n = 3424; Rotterdam study, n = 3847; Age, Gene, Environment and Susceptibility-Reykjavik, n = 2193). Meta-analysis showed strong replication for a genetic influence on serum bilirubin levels of the UGT1A1 locus (P < 5 x 10(-324)) and a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
192
3
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(227 citation statements)
references
References 36 publications
26
192
3
6
Order By: Relevance
“…We robustly reproduced two associations between ADME genes and physiological traits: ABCG2 and gout and SLCO1B1 and jaundice [47,49]. The remaining replications are signals driven by the impact of ADME variants on the metabolism of xenobiotics (CYP2A6 on nicotine, CYP2C19 and NAT1 on carcinogens).…”
Section: Adme Phewas Replicates Single Trait Associationsmentioning
confidence: 70%
See 1 more Smart Citation
“…We robustly reproduced two associations between ADME genes and physiological traits: ABCG2 and gout and SLCO1B1 and jaundice [47,49]. The remaining replications are signals driven by the impact of ADME variants on the metabolism of xenobiotics (CYP2A6 on nicotine, CYP2C19 and NAT1 on carcinogens).…”
Section: Adme Phewas Replicates Single Trait Associationsmentioning
confidence: 70%
“…In previous studies of European populations, rs4149056 has been associated with elevated serum bilirubin concentrations [49], a known cause of jaundice. The CAF was 0.23 for cases (n = 154) and 0.15 for controls (n = 5058).…”
Section: Replicating Associationsmentioning
confidence: 89%
“…Concurrent elevations of transaminases were not seen in these six patients. A recent genome-wide association study identified OATP1B1 (alternative symbol SLCO1B1) as one of the top loci associated with bilirubin levels (Johnson et al, 2009). Genetic markers in the OATP1B1 gene were also evaluated in this study and were not found to be associated with pazopanib-related bilirubin elevation.…”
Section: Discussionmentioning
confidence: 93%
“…Corroboratively, recent pharmacogenetic studies have linked polymorphisms in the SLCO1B1 and SLCO1B3 genes with unconjugated and conjugated plasma bilirubin levels (Johnson et al, 2009;Sanna et al, 2009;Zhang et al, 2007). A role of Oatps in hepatocellular bilirubin uptake is further supported by experiments with mice with deleted Slco1a and Slco1b genes.…”
Section: Bilirubinmentioning
confidence: 95%